The concrete Euro implementing monetary policy in the Euro area - Mercier, Paul.; Papadia, F. (Oxford : Oxford University Press, 2011)
The Euro area's framework for monetary policy implementation was introduced in 1999. 11 years on, this volume examines the theoretical and historical underpinnings of the framework, how it has fared in practice, and what challenges it is likely to face in the future.
Description based on online resource; title from PDF title page (viewed on May 11, 2011).
Includes bibliographical references and index.
Keywords: Monetary policy -- European Union countries; Euro area